Dorema Aucheri and exercise training in enhancing PPARγ/mTOR/PI3K gene expression in muscle tissue of hypothyroid mice: experimental approaches using a hypothyroid mouse model - Malihe Bakhti; Farzaneh Taghian; Khosro Jalali Dehkordi; Rezvan Mirsafaei Rizi (Jorjani Biomedicine Journal)
Background: Hypothyroidism is typically associated with a decreased basal metabolic rate, reduced energy expenditure, and weight gain. Exercise training and Dorema Aucheri (DA) have been identified as beneficial therapeutic strategies within complementary health approaches. Skeletal muscle metabolism and fiber type are regulated by innervation and soluble factors, such as thyroid hormones. However, the mechanisms between muscle function and hypothyroidism remain unclear. Methods: Thirty mice were divided into five subgroups: the normal group; hypothyroid mice (HYPO, 8 mg/kg of propylthiouracil administered via intraperitoneal injection for 30 days); hypothyroid mice treated with DA (gavaged at 0.4 mg/kg for two months, five days per week); hypothyroid mice treated with exercise (75% VO2 max, 45 minutes per session, for two months, five days per week); and hypothyroid mice treated with both DA and exercise. The mRNA expression levels were detected via real-time qPCR. Results: The data indicated that PPARγ, mTOR, and PI3K levels are reduced in hypothyroidism. DA and exercise enhanced PPARγ, mTOR, and PI3K levels in muscle tissue. Notably, DA and exercise significantly increased the expression levels of PPARγ, mTOR, and PI3K. Conclusion: Exercise and DA, as alternative and complementary medicine, modified the PPARγ/mTOR/PI3K signaling pathways affected by hypothyroidism in mice.